The dilemma of group membership in the internet age - Vähämaa, Miika (Javnost (Ljubljana), 2014)
A commonly accepted assumption is that scientific knowledge on the part of the general public would increase in an era of increasing ease of access to all forms of information. This argument suggests that the public only needs to take an advantage of an inexpensive laptop computer to be superbly informed. However, what appears to be the case is that the public appears to be more prone than ever to misinformation, partial truths, and "spin". Research shows that, even when it comes to scientific knowledge, we have socially-mediated preferences; we prefer those beliefs that we like and that are considered reasonable by our peers. Importantly, our "peers" can in our hyperlocal world be virtual or real. Thus, social group membership merges with our individual likes and dislikes to shape what we take as "knowledge". Groups, therefore, become platforms of social epistemologies. We examine our argument from the viewpoint of the United States using a large data set from the General Social Survey. We employ the 2008 topical module to examine the relationships between attitudes and knowledge concerning science and technology, the relationship between media use, demographic group variables, and group-related attitudes toward science.
Keywords: svetovni splet; družbene skupine; družbena omrežja; communication; komuniciranje; informacije; knowledge; znanje; znanstvene informacije; navidezna resničnost